A new Culicoides from The Amazonian Region, Brazil (Diptera: Ceratopogonidae) - Maria Luiza Felippe-Bauer; Rosana de S Veras; Eloy G Castellon; Nancy A Moreira (Memorias do Instituto Oswaldo Cruz, 2000)
A new Neotropical species of biting midge Culicoides (Haematomyidium), C. kampa Felippe-Bauer, Veras & Castellon, is described and illustrated based on female specimens from the Amazonian Region.